2012
DOI: 10.1094/mpmi-12-11-0322
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glutamine Synthetase by Phosphinothricin Leads to Transcriptome Reprograming in Root Nodules of Medicago truncatula

Abstract: Glutamine synthetase (GS) is a vital enzyme for the assimilation of ammonia into amino acids in higher plants. In legumes, GS plays a crucial role in the assimilation of the ammonium released by nitrogen-fixing bacteria in root nodules, constituting an important metabolic knob controlling the nitrogen (N) assimilatory pathways. To identify new regulators of nodule metabolism, we profiled the transcriptome of Medicago truncatula nodules impaired in N assimilation by specifically inhibiting GS activity using pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 120 publications
1
38
0
Order By: Relevance
“…However, all the NCR genes without exception are reduced in expression by the senescence-inducing treatments, in agreement with a recent report [30]. The downregulation of NCR gene expression is induced very rapidly, within 4 hours of nitrate application [30] or 8 hours of phosphinothricin treatment (Additional file 2: Figure S5) and occurs before the degeneration of the symbiotic cells and their bacterial symbionts [29]. The down-regulation of the NCRs most likely reflects the shutdown of the symbiotic process.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, all the NCR genes without exception are reduced in expression by the senescence-inducing treatments, in agreement with a recent report [30]. The downregulation of NCR gene expression is induced very rapidly, within 4 hours of nitrate application [30] or 8 hours of phosphinothricin treatment (Additional file 2: Figure S5) and occurs before the degeneration of the symbiotic cells and their bacterial symbionts [29]. The down-regulation of the NCRs most likely reflects the shutdown of the symbiotic process.…”
Section: Resultssupporting
confidence: 89%
“…Nodule senescence leads to a complete digestion of the bacteroids and the symbiotic host cells and is controlled by the transcriptional activation of a battery of genes which are involved the digestion of macromolecules and the remobilization of the liberated nutrients [28]. To test whether NCR genes are induced by senescence, we analyzed their expression in nitrate or herbicide induced senescent nodules [20, 29] (Figure 4; Additional file 2: Figure S5). Besides the NCR genes, 8 senescence marker genes were included in the analysis (Additional file 1: Table S1) [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has been shown that nodules formed by the hmp - mutant rhizobium suffer a premature senescence induced by NO (Cam et al, 2012), it is tempting to speculate that the NO-induced GS inhibition could be associated with this premature nodule senescence. This idea is supported by the finding that the application of the GS inhibitor phosphinothricin (PPT) to root nodules promotes nodule senescence (Seabra et al, 2012). …”
Section: Physiological Significance Of Gs Nitration For Root Nodule Fmentioning
confidence: 95%
“…NO plays a crucial role in many physiological and pathological processes, including platelet activation and adhesion, vasodilation, wound healing, and inflammation . Because NO is a natural antimicrobial agent, it has been incorporated into different medical grade polymers to not only improve the hemocompatibility but also prevent infection in blood‐contacting devices such as sensors, catheters, vascular grafts, extracorporeal circuits and in medical device coatings . Moreover, NO releasing polymers have not been reported to cause any hemocompatibility, biocompatibility, or long‐term storage stability issues …”
Section: Introductionmentioning
confidence: 99%